Efeitos de acoplamento térmico nas técnicas de lente térmica e espelho térmico - Lukasievicz, Gustavo Vinicius Bassi (2014)
This work presents a theoretical and experimental study in Thermal Lens (TL) and Thermal Mirror (TM) techniques by taking sample-fluid heat coupling into account. The heat conduction equation is solved to obtain a semi-analytical solution to the temperature in the sample and in the surrounding fluid in the case of continuous and pulsed laser excitation. The thermoelastic equation is used to obtain the displacement induced on the sample surface. The solutions to the temperature and surface displacement, for samples with low optical absorption ( - ) and high optical absorption ( - ), are in excellent agreement with the results obtained using Finite Element Method (FEM). The solutions are used to model the TL and TM effects considering the contribution of the sample and the fluid. The heat transfer between the sample and the air coupling fluid does not introduce an important effect over the induced probe beam phase shift when compared to the solution obtained without considering axial heat flux, unless to extremely thin samples. However, when using water as the surrounding fluid, heat coupling led to a significant effect in fluid phase shift. Experimental results using stainless steel in air and water are used to demonstrate the potentiality of the TM technique to determine the thermal properties of both the sample and the fluid. A theoretical analysis of the pulse laser profile in the TM technique is presented. TM experiments performed in optical glasses show that the technique is useful for quantitative determination of the thermal diffusivity of materials with low optical absorption.